The predatory mite Typhlodromalus aripo prefers greenmite induced plant odours from pubescent cassava varieties - Onzo, A.; Hanna, R.; Sabelis, M.W. (Springer, 2012)
It is well known that plant-inhabiting predators use herbivore-induced plant volatiles to locate herbivores being their prey. Much less known, however, is the phenomenon that genotypes of the same host plant species vary in the attractiveness of these induced chemical signals, whereas they also differ in characteristics that affect the predator’s foraging success, such as leaf pubescence. In a series of two-choice experiments (using a Y-tube olfactometer) we determined the preference of Typhlodromalus aripo for pubescent versus glabrous cassava cultivars infested with the cassava green mite Mononychellus tanajoa and also the preference for cultivars within each of the two groups. We found that when offered a choice between pubescent and glabrous cassava cultivars (either apex or leaves), T. aripo was significantly more attracted to pubescent cultivars. For each cultivar, M. tanajoa infested leaves and apices were equally attractive to T. aripo. There was however some variation in the response of T. aripo to M. tanajoa-infested plant parts within the group of pubescent cultivars, as well as within the group of glabrous cultivars. Our study confirms not only that T. aripo uses herbivore-induced plant volatiles to search for prey in cassava fields, but it also shows that it can discriminate between glabrous and pubescent cultivars and prefers the latter. This knowledge can be useful in selecting cultivars that are attractive and suitable to T. aripo, which, in turn, may promote biological control of the cassava green mite.